2012
DOI: 10.1016/j.addbeh.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled trial to test the efficacy of an online, parent-based intervention for reducing the risks associated with college-student alcohol use

Abstract: Alcohol consumption among college students remains a major public health concern. Universal, Web-based interventions to reduce risks associated with student alcohol consumption have been found to be effective in changing their alcohol-related behavior. Recent studies also indicate that parent-based interventions, delivered in booklet form, are effective. A parent-based intervention that is also Web-based may be well suited to a dispersed parent population; however, no such tool is currently available. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 25 publications
0
28
1
Order By: Relevance
“…Donovan and colleagues (2012) demonstrated that a four-week web-based PBI could change parents’ communication about protective behavioral strategies. The current study is the first to test the potential effectiveness of a shorter intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donovan and colleagues (2012) demonstrated that a four-week web-based PBI could change parents’ communication about protective behavioral strategies. The current study is the first to test the potential effectiveness of a shorter intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The Internet is increasingly used to deliver health and risk behavior information due to cost-effectiveness, ability to personalize information, and accessibility (Muñoz et al, 2006;Strecher, Shiffman, & West, 2005). To our knowledge, Donovan et al (2012) is the only study to date to specifically explore the efficacy of a web-based PBI. In this study, parents of college students took part in a four-week web-based intervention that aimed to enhance parent communication skills and provide information on ways to discuss protective behavioral strategies (PBS) used to reduce negative consequences associated with drinking.…”
Section: Introductionmentioning
confidence: 99%
“…There has also been some success in addressing college-aged substance use by involving parents through providing this kind of information. For example, "My Student Body program," an online intervention for parents of college students (Donovan, Wood, Frayjo, Black, & Surette, 2012) and the "Parent-Based Intervention" program, where parents were sent a handbook by mail with information on alcohol abuse among college students and its effects, techniques for improving parent-teen communication, and advice on how to help teens become more assertive and resist peer pressure (Turrisi et al, 2013).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Smit et al, 2008;Kaminski, Valle, Filene & Boyle, 2008) indicated that these interventions have demonstrated efficacy in preventing substance use and other child problem behaviors. These positive results have been reported in different settings (Aalborg et al, 2010;Letarte, Normandeau & Allard, 2010;Redmond et al, 2009;Henggeler & Schoenwald, 2011;Brook, McDonald & Yan, 2012;Donavan, Wood, Frayjo, Black & Surette, 2012), target groups (Mindel & Hoefer, 2006;Orte, Touza, Ballester & March, 2008;McDaniel, Braiden, Onyekwelu, Murphy & Regan, 2011;Posthumus, Raaimakers, Maassen, Engeland, & Matthys, 2012;Kumpfer, Whiteside, Greene & Allen, 2010), cultures (Skärstrand, Larsson & Andréasson, 2008;Pérez, et al, 2009;Kumpfer, Xie & O'Driscoll, 2012;Brotman et al, 2009;Ortega, Giannotta, Latina & Ciairano, 2012) and addicted behaviours (Trudeau, Spoth, Randall & Azevedo, 2007;Zhong, et al, 2011;Donovan et al, 2012). …”
Section: Objeto Y Alcance De La Presente Revisión Bibliográficamentioning
confidence: 75%